Enhancing business continuity and it capability : system administration and server operating platforms /: system administration and server operating platforms. (2020) - Bajgorić, Nijaz; Turulja, Lejla, 1981-; Ibrahimovic, Semir, 1969-; Alagic, Amra, 1976-
No abstract available